2011
DOI: 10.1016/j.biomaterials.2010.08.106
|View full text |Cite
|
Sign up to set email alerts
|

An injectable thiol-acrylate poly(ethylene glycol) hydrogel for sustained release of methylprednisolone sodium succinate

Abstract: Clinically available injectable hydrogels face technical challenges associated with swelling after injection and toxicity from unreacted constituents that impede their performance as surgical biomaterials. To overcome these challenges, we developed a system where chemical gelation was controlled by a conjugate Michael addition between thiol and acrylate in aqueous media, with 97% monomer conversion and 6 wt.% sol fraction. The hydrogel exhibited syneresis on equilibration, reducing to 59.7% of its initial volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 40 publications
3
116
0
Order By: Relevance
“…This polymer was proposed for use in injectable drug formulations [15]. We were interested in the performance of the enzyme under non-buffered conditions at room temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This polymer was proposed for use in injectable drug formulations [15]. We were interested in the performance of the enzyme under non-buffered conditions at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The thiol-acrylate hydrogel was originally proposed as a base-catalyzed polymerization for injectable drug formulations [15] and this recipe was subsequently modified to obtain gelation after a programmable time lag using the increase in pH of the urea-urease reaction [9]. Here we further modified the formulation with the addition of PVA in order to obtain gel beads using emulsion polymerisation.…”
Section: Thiol-acrylate Hydrogel Beadsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar PEG‐based hydrogel to the one constructed in this study was demonstrated to undergo hydrolytic degradation over the course of weeks, thus resulting in controlled drug release 23. More recently, a method for the pH control of the self‐assembly and disassembly of peptide hydrogels was proposed for fluidic guidance in channels and self‐erasing rapid prototyping 28…”
mentioning
confidence: 83%
“…A custom made two component cross-linked hydrogel (PEG) consisting of 20 wt.% poly (ethylene glycol) in phosphate buffered saline (PBS) was prepared by mixing PEGDA in PBS into ETTMP-1300 in PBS [30]. PEG is a synthetic water-soluble polymer approved by the FDA for biomedical use in different applications including injectable hydrogels.…”
Section: Gelsmentioning
confidence: 99%